VARIABLE INERTIA FLYWHEEL - JACOBSON EVAN E (2016)
A flywheel including a rim having a circular shape, a first hub disposed coaxially within the rim, and at least two spokes having a first end coupled to the rim, and a second end coupled to the first hub. A second hub disposed coaxially with the rim, and having at least one guiding member. The at least one guiding member having a slot. The flywheel includes at least two assemblies corresponding to the at least two spokes, such that one of the at least two assemblies is coupled to one of the at least two spokes. A first weight having at least one protruding member. A spring member disposed adjacent to the first weight, and a support member disposed adjacent to the spring member. A weight assembly including at least one second weight and a mount member. The flywheel including an actuator coupled to the second hub.